Managing without growth slower by design, not disaster - Victor, Peter A., 1946-; Edward Elgar Publishing (Cheltenham ; Northampton, Mass. : Edward Elgar, 2008)
Peter Victor challenges the priority that rich countries continue to give to economic growth as an over-arching objective of economic policy. The challenge is based on a critical analysis of the literature on environmental and resource limits to growth, on the disconnect between higher incomes and happiness, and on the failure of economic growth to meet other key economic, social and environmental policy objectives. Shortly after World War II, economic growth became the paramount economic policy objective in most countries, a position that it maintains today. This book presents three arguments on why rich countries should turn away from economic growth as the primary policy objective and pursue more specific objectives that enhance wellbeing.
The idea of economic growth -- Why manage without growth? -- Systems, information and prices -- Limits to growth : sources -- Limits to growth : sinks and services -- Limits to growth : synthesis -- Scale, composition and technology -- Economic growth and happiness -- The disappointments of economic growth -- Managing without growth in Canada : exploring the possibilities -- Policies for managing without growth.
Includes bibliographical references (p. 225-252) and index.
Keywords: Economic development -- Social aspects; Economic development -- Environmental aspects; Electronic books